EXECUTIVE POLICIES FORMULATION OF COERCIVE EFFORTS USAGE AS POLICE DISCRETION AT THE ARRESTING STAGE OF TERRORISM CRIMINAL SUSPECTS - Dedi Prasetyo (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThe arresting action that is done to the suspect of terrorism determined by the understanding about the prevailing law and morality and SOP (Standard Operational Procedure) that has been determined to enforce justice. The givenauthority should not oppose with Human Rights, to determine the abuse in thediscretion at the arrest stage by using whether the authority usage deviates fromthe authority giver and whether the abuse of power has occurred or not, thenthe parameters that can be used are rationality principles. As the guidance or foundation for Indonesian Police member to do the police discretion suitable with the main tasks and authorities that contained Article 18 subsection (1) and (2) of Law No 2 Year 2002, that is: (1) For public interest, Indonesian Republic in conducting their tasks and authorities can act according to their own assessments. (2) The stipulation implementation as given in the subsection (1) only can be done in the very urgent condition by considering legislation and profesional ethics code of Indonesian Police. Some articles in the Perkap No 1 and 8 Year 2009 still can be categorized as multi interpretation and not measured clearly where the implementation in field able to produce abuse of power. Especially for the term usage of suspect stop contained at the Perkap. The term of stop according to the Indonesian big dictionary means to stop, to finish, to make (cause) stop (stop means not move). In the law enforcement practice relates with the terrorism arrest has occurred abuse of authorities if not based on rationality and the understanding and implementation of true legal norms that will influence the law enforcement that can not be answered in moral and accountable. Effort to eradicate the terrorism criminal offense should be followed by executive policy formulation as the clear, firm and measured Fixed Procedure so each power usage in the police action especially firearms can be answered based on human rights, Code of Conduct for Law Enforcement Officials and Basic Principle on the Use of Force and Firearms by Law Enforcement Officials, by omitting the use of stop term in the usage of firearms and replaced by immobilize and give clear variable about the term of life safety threats (opennorms should be avoided to avoid the multi interpretation) , should implementLex Certaf principle, the formulation should be certain, concise.Keywords: policy formulation, coercive efforts, discretion